Preseason Assessment of Radiographic Abnormalities in Elbows of Little League Baseball Players. (4th May 2016) - Pennock, Andrew T.; Pytiak, Andrew; Stearns, Phillip; Roocroft, Joanna H.; Dwek, Jerry; Kruk, Peter; Bastrom, Tracey P.
Abstract : Background: Youth baseball has been associated with elbow pain and elbow abnormalities, leading to the implementation of throwing and pitching guidelines. The purpose of the current study was to examine elbow abnormalities on magnetic resonance imaging (MRI) in asymptomatic Little League baseball players and to correlate these findings with the players' throwing history and physical examinations. Methods: A prospective study of Little League players who were 10 to 13 years of age was performed. Players were recruited prior to the start of the season and underwent bilateral elbow MRI. All players underwent a physical examination and responded to a questionnaire addressing their playing history and any arm pain. The MRIs were read by 2 radiologists. Responses on the questionnaire and physical examination findings were compared between subjects with and without positive MRI findings utilizing chi-square and analysis of variance techniques. Results: Twenty-six players were enrolled. The majority (77%) were right-handed and 14 (54%) were a pitcher and/or catcher. Nine players (35%) had 12 positive MRI findings: 7 findings of edema or signal change of the medial epicondyle apophysis, 2 findings of fragmentation of the medial epicondyle, and 3 findings of edema or signal change of the sublime tubercle. The prevalence of positive MRI findings and a history of arm pain were not greater in pitchers and catchers compared with other players. Players with a positive MRI finding demonstrated greater reduction in shoulder internal rotation (12°) compared with the nondominant arm (3°) (p = 0.04). The two factors associated with a positive MRI finding were year-round play (47% of year-round players compared with 11% of non-year-round players; p < 0.01) and working with a private coach (71% compared with 21%; p = 0.02). Additionally, a history of pain was associated with year-round play and a private coach (p < 0.05). Conclusions: MRI abnormalities involving the medial aspect of the elbow are common in year-round Little League baseball players, especially those with internal rotation deficits and private coaches. Although Little League guidelines potentially lessen abnormalities seen in pitchers, further refinement of these guidelines addressing year-round play, pain, and private coaching should be considered. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.